2020
DOI: 10.15376/biores.15.1.1397-1406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of papermaking conditions on the ink absorption and overprint accuracy of paper

Abstract: The ink-absorption capacity is an important factor for evaluating the printing quality of paper. In this study, the effects of different parameters of papermaking on the ink-absorption capacity of paper were investigated. The results showed that hardwood pulp exhibited better performance in increasing the absorptivity of paper compared with softwood pulp. When the content of hardwood pulp in paper was increased from 0% to 100%, the ink mark length decreased from 5.1 cm to 4.3 cm. Furthermore, a basis weight ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Paper is a compelling choice: it is sustainable, biodegradable, highly recycled, and more cost effective (∼0.1 cent dm −2 ) compared to commonly used plastics such as PET (≈2 cent dm −2 ) and PI (∼30 cent dm −2 ) [12]. Nonetheless, paper substrates have not yet replaced plastics because the porous microstructure of paper causes the imbibition and wicking of functional inks, which compromises printability and resolution [12][13][14][15][16][17][18]. Furthermore, an ideal green process for end-of-life recycling should separate and reuse electronic materials and recycle the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Paper is a compelling choice: it is sustainable, biodegradable, highly recycled, and more cost effective (∼0.1 cent dm −2 ) compared to commonly used plastics such as PET (≈2 cent dm −2 ) and PI (∼30 cent dm −2 ) [12]. Nonetheless, paper substrates have not yet replaced plastics because the porous microstructure of paper causes the imbibition and wicking of functional inks, which compromises printability and resolution [12][13][14][15][16][17][18]. Furthermore, an ideal green process for end-of-life recycling should separate and reuse electronic materials and recycle the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Papers made from hardwood exhibit higher ink absorption abilities and overprinting precision. This is attributed to a higher content of fine fibers [25]. In addition, while shorter fibers exhibit less flexibility and slenderness ratio, short and thick fibers show even poorer values [26].…”
Section: Review 4 Of 25mentioning
confidence: 98%
“…The ink absorption capacity of paper can be influenced by parameters such as the type of pulp used, basis weight, sizing agent, and beating degree [52]. For example, research performed by Dong et al showed hardwood pulp exhibits a higher performance in terms of paper absorptivity compared to softwood pulp [53].…”
Section: Properties Of Paper Substratesmentioning
confidence: 99%